Birth weight of indigenous children in Brazil: results of the First National Survey of Indigenous People's Health and Nutrition - Aline Alves Ferreira; Mirian Carvalho de Souza; Andrey Moreira Cardoso; Bernardo Lessa Horta; Ricardo Ventura Santos; James R. Welch; Carlos E. A. Coimbra Jr (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Birth weight is an important predictor of perinatal, infant, and preschool-age children morbimortality. However, information about indigenous children's birth weight is still scarce. This study aimed to analyze the birth weight of indigenous children based on data from the First National Survey of Indigenous People's Health and Nutrition, Brazil (2008-2009). This is the first study to address indigenous children's birth weight based on a nationwide representative sample. Mean birth weights and the respective standard deviations were calculated according to geopolitical region, sex, type of birth, and birthplace. The chi-square test was used to analyze differences in proportions, and Kruskal-Wallis and Mann-Whitney U tests in means, considering sample design and data normality. We found no records on birth weight in the researched documents for 26.7% of the 6,128 sampled children. The mean birth weight for the 3,994 children included in the analyses was 3,201g (standard deviation - SD ± 18.6g), regardless of sex, type of birth, and birthplace. The prevalence of low birth weight was 7.6% (n = 302) and was significantly higher among girls. Boys presented significantly higher mean birth weight than girls, regardless of the geopolitical region. Low birth weight was slightly less frequent among indigenous children when compared to Brazilian children in general. Our study indicates the need to improve prenatal care and the quality of consultation records for indigenous women as a strategy to promote safe pregnancy and childbirth.